The increased tendency for anemia in traditional Chinese medicine deficient body constitution is associated with the gut microbiome - Liang, Yuanjun; Chen, Yang; Lin, Yanzhao; Huang, Wei; Qiu, Qinwei; Sun, Chen; Yuan, Jiamin; Xu, Ning; Chen, Xinyan; Xu, Fuping; Shang, Xiaoxiao; Deng, Yusheng; et al. (Frontiers in Nutrition, 2024)
Background Constitution is a valuable part of traditional Chinese medicine theory; it is defined as the internal foundation for the occurrence, development, transformation and outcome of diseases, and has its characteristic gut microbiota. Previous study showed that deficiency constitution was related to lower Hb counts. However, no research has examined how alterations in the gut microbiome induced by deficiency constitution may increase the tendency for anemia. Methods We used a multiomics strategy to identify and quantify taxonomies and compounds found under deficient constitution individuals and further explore the possible pathological factors that affect red blood cell indices. Results ① People with deficient constitution showed lower hemoglobin (Hb), more Firmicutes, less Bacteroidetes, and higher α diversity. ② We identified Escherichia coli, Clostridium bolteae, Ruminococcus gnavus, Streptococcus parasanguinis and Flavonifractor plautii as potential biomarkers of deficient constitution. ③ Slackia piriformis, Clostridium_sp_L2_50 and Bacteroides plebeius were enriched in balanced-constitution individuals, and Parabacteroides goldsteinii was the key bacterial marker of balanced constitution. ④ Flavonifractor plautii may be a protective factor against the tendency for anemia among deficient individuals. ⑤ Ruminococcus gnavus may be the shared microbe base of deficiency constitution-related the tendency for anemia. ⑥ The microorganism abundance of the anaerobic phenotype was lower in deficient constitution group. ⑦ Alterations in the microbiome of deficient-constitution individuals were associated with worse health status and a greater risk of anemia, involving intestinal barrier function, metabolism and immune responses, regulated by short-chain fatty acids and bile acid production. Conclusion The composition of the gut microbiome was altered in people with deficient constitution, which may explain their poor health status and tendency toward anemia.